Ecologizing Knowledge: Considerations to Rethink Life in the Ever-Changing World Triggered by the Pandemic (Global Journal of Human-Social Science, 2021)
We present a theoretical essay approaching the question: according to which paradigm will we reorganize ourselves as a human society facing the experience of the Pandemic? To ecologize knowledges by articulating and establishing relations among different theories and forms of knowledge, we offer clues and possibilities to create forms of acting in life, especially in education practices, taking this moment we are living in as a trigger for transformations. In this way, we suggest the method of complexity as a strategy to redimension our way of understanding what we are living and transforming our way of acting. We emphasize the need of overcoming the current objectivism and rationalism, and proposing the systemic vision that includes the reflective, active, strategist subject as co-creator of the reality in which he lives. In this way, we suggest that educational practices need to be configured as a cognitive ecology, the result of the articulation of various contexts, coexistence scenarios, where teachers and students act together, taking care of each other and co-creating learning contexts in the experience. This approach can give rise to a form of education founded on a dynamic based on cooperating and sharing in circularity, surpassing control and judgment and enhancing the empowerment of being.
Keywords: ecology of knowledges; complexity; systemic vision; education practices; pandemic